2015
DOI: 10.1097/htr.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment in the United States After Traumatic Brain Injury for Working-Age Individuals

Abstract: Objective To estimate the prevalence of unemployment and part-time employment in the United States for working-age individuals completing rehabilitation for a primary diagnosis of traumatic brain injury (TBI) between 2001 and 2010. Design Secondary data analysis. Setting Acute inpatient rehabilitation facilities. Participants Patients aged 16 to 60 years at injury who completed inpatient rehabilitation for TBI between 2001 and 2010. Main Outcome Measures Unemployment; Part-time employment. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 35 publications
0
62
0
2
Order By: Relevance
“…Ponsford and Spitz [11] also noted these challenges impact the capacity for employment among individuals who incur a TBI while they are young. Cuthbert et al [3] likewise stated "the adverse outcomes associated with TBI can have a substantial impact on a person's ability to assume gainful employment after injury." One particular area of difficulty noted by Harris et al [12] involved the inability of individuals with a TBI to accurately recall their previous work history.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ponsford and Spitz [11] also noted these challenges impact the capacity for employment among individuals who incur a TBI while they are young. Cuthbert et al [3] likewise stated "the adverse outcomes associated with TBI can have a substantial impact on a person's ability to assume gainful employment after injury." One particular area of difficulty noted by Harris et al [12] involved the inability of individuals with a TBI to accurately recall their previous work history.…”
Section: Introductionmentioning
confidence: 99%
“…Because these challenges can impact the ability of a person to successfully work after a TBI, employment status is an important measure of successful rehabilitation and recovery [10]. Cuthbert et al [3] found that of 93 participants, the probabilities of being employed 1 year post-injury were 95% lower in participants who were unemployed prior to the injury, 74% lower for participants with more severe damage, and 82% lower for participants with more significant cognitive limitations. The rates of employment vary from study to study, but most researchers agree that the rate of unemployment and underemployment increases after a TBI is sustained and that this trend continues over time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations